2020
DOI: 10.1158/1535-7163.mct-20-0149
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Multiple EGFR-expressing Tumors with a Highly Potent Tumor-selective Antibody–Drug Conjugate

Abstract: ABBV-321 (serclutamab talirine), a next-generation EGFRtargeted antibody-drug conjugate (ADC) incorporates a potent pyrrolobenzodiazepine (PBD) dimer toxin conjugated to the EGFRtargeting ABT-806 affinity-matured AM1 antibody. ABBV-321 follows the development of related EGFR-targeted ADCs including depatuxizumab mafodotin (depatux-m, ABT-414), ABT-806 conjugated to monomethyl auristatin F (MMAF), and ABBV-221 (losatuxizumab vedotin), AM1 antibody conjugated to monomethyl auristatin E (MMAE). The distinct tumor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…ABT-806 is a humanized, tumor-specific anti-EGFR IgG1 monoclonal antibody [ 527 ]. The antibody–drug conjugates (ADCs) ABT-414 (depatuxizumab mafodotin) [ 528 ] and ABBV-321 (serclutamab talirine) [ 529 ] are composed of the antibody ABT-806 conjugated to the cytotoxic monomethyl auristatin F (MMAF) and the affinity-maturated version of ABT-806 conjugated to an ultrapotent pyrrolobenzodiazepine dimer, respectively. Navitoclax (ABT-263) is a small-molecule inhibitor of BCL-xL, BCL2, and BCL2L2 with anticancer activity [ 433 ].…”
Section: Combination Strategy For Overcoming Egfri Resistance In Tnbcmentioning
confidence: 99%
“…ABT-806 is a humanized, tumor-specific anti-EGFR IgG1 monoclonal antibody [ 527 ]. The antibody–drug conjugates (ADCs) ABT-414 (depatuxizumab mafodotin) [ 528 ] and ABBV-321 (serclutamab talirine) [ 529 ] are composed of the antibody ABT-806 conjugated to the cytotoxic monomethyl auristatin F (MMAF) and the affinity-maturated version of ABT-806 conjugated to an ultrapotent pyrrolobenzodiazepine dimer, respectively. Navitoclax (ABT-263) is a small-molecule inhibitor of BCL-xL, BCL2, and BCL2L2 with anticancer activity [ 433 ].…”
Section: Combination Strategy For Overcoming Egfri Resistance In Tnbcmentioning
confidence: 99%
“…The ability of ADCs to deliver highly potent payloads in the targeted cancer cell (e.g., with EGFR expression) with reduced off-target toxicity makes this approach very attractive in the management of MM. We have previously reported that mAb806-ADC has markedly superior antitumor efficacy in animal models compared to antibody alone and the drug alone at similar concentrations [21]. The ability of mAb806 ADCs to target a conformational epitope exposed in tumor-specific conditions allows effective tumor targeting without the conventional EGFR inhibitor-mediated toxicities [13].…”
Section: Discussionmentioning
confidence: 99%
“…ABBV-221 was evaluated in a phase I clinical trial in patient EGFR-expressing solid tumors [19,20]. ABBV-322 is another mAb806-ADC derivative, comprised of the nonaffinity matured version of ABT-806 engineered to include an S238C point mutation that permits site-specific conjugation to a DNA minor groove crosslinking agent, pyrrolobenzodiazepine (PBD), via a cathepsin-cleavable Val-Ala linker with a DAR of two [15,18,21,22] (Supplementary Figure S1).…”
Section: Introductionmentioning
confidence: 99%
“…Binding kinetics of ABBV-176 and the h16f parental mAb to recombinant human and cynomolgus PRLR ECD were determined by surface plasmon resonance-based measurements made on Biacore T200 instrument (GE Healthcare) using previously described methods [ 22 ].…”
Section: Methodsmentioning
confidence: 99%